Total Food Utilization and Its Impact on Human Health - Cardoso, Fabiane Toste; Fróes, Silvana Camello; Friede, Reis; de Miranda, Maria Geralda; Chagas, Carla Junqueira; Avelar, Kátia Eliane Santos (Sustainability in Debate, 2015)
Hunger and food waste are two significant health problems in Brazil. They are two of the paradoxes in the country, which is one of the world’s major food exporters and, at the same time, a champion in food waste. This study, which is based on literature review, addresses the importance of the integral utilization of food and its relation to human health and the environment. Results point out that families could in fact use wasted food to alleviate hunger and malnutrition through the development of simple, nutritive meals at the household level. Integral food utilization can also contribute to the reduction of the environmental impact caused by food waste.